Unemployment and emigration in Italy in the light of the E.R.P. and O.E.E.C. - COSMO, G. (PSL Quarterly Review, 2014)
The article deals with one of the most delicate aspects of the present Italian economic situation, that of the labour market seen both from the standpoint of unemployment and of emigration. The author recalls the weight and importance these two factors have had in the development of Italian economy; he makes a brief analysis of the causes that have led to the present aggravation of the situation, arising both from the upheavals due to the war and international political uncertainties, and he tries to foresee probable developments as affected by the reconstruction plans to be carried out with E.R.P. help. The author is led to the conclusion that Italy’s excess of workers presents a problem that cannot be solved by action limited to the structural changes in the Italian economy; a large current of emigration is essential, and this requires the active co-operation of the several countries concerned. JEL: E24, J22